Ryzyko zmaskulinizowania kobiet w dziedzinach ścisłych i technicznych - Szymczak, Emilia (Studia Edukacyjne, 2017)
Article entitled The Risk of Masculinization of Women in Science and Engineering focuses on the problem of women’s acceptance of male models and standards of behavior as a consequence of operating in the traditionally male work environment. It attempts to answer the question whether women working in the fieldsof engineering and science experience the need to get rid of or temporarily hide their essential femininity to efficientlyperform their work and meet the obligations arising from their chosen career.